Using the Jigsaw Technique to Teach Clinical Controversy in a Clinical Skills Course - Phillips, Jennifer (Am J Pharm Educ, 2015)
Objective. To evaluate the effectiveness and student perception of the jigsaw technique to engage students in a clinical controversy exercise and to assess student engagement level during each step of the process. Design. Students were assigned individual readings pertaining to the controversy surrounding the drug oxybutynin switching from prescription to nonprescription. They met with an expert group and teaching groups during mandatory laboratory time and worked together to formulate a recommendation on the appropriateness of nonprescription conversion for a drug. Assessment. A quiz taken individually was used to measure effectiveness. Student perception and level of engagement was assessed using surveys. Conclusion. The jigsaw technique was successful in teaching the concepts involved in the clinical controversy. Group members rated themselves and fellow participants’ level of engagement as high during both the expert group and teaching group sessions. Most students reported they learned about the same or more with the jigsaw technique compared to another cooperative learning technique used in the curriculum.